Emotion Regulation Processes Can Benefit Self-Regulated Learning in Classical Musicians - Peistaraite, Ugne; Clark, Terry (Frontiers in Psychology, 2020)
Self-regulated learning (SRL) is the degree to which students are metacognitively, motivationally, and behaviourally active participants in their own learning process. It involves the self-regulation of cognitive, behavioural, and affective processes. SRL holds significant potential for enhancing practice and achievement. Although affect is acknowledged as one of the three fundamental processes in SRL, there is limited research investigating it. However, emotions have been found to influence SRL efficiency while emotion regulation (ER) can impact learning outcomes. Thus, this study sought to investigate how ER processes relate to SRL among professional musicians who perform Western classical music. Four forms of regulation (reappraisal, suppression, rumination, repression) were examined in relation to the SRL three-phase model. Professional musicians (N = 334) of 39 nationalities (age: 18–66; [M = 28]; female = 215; male = 119) completed a survey comprising the Self-Regulated Learning in Musicians Questionnaire, the Emotion Regulation Questionnaire, and demographic items. A significant positive correlation emerged between SRL and reappraisal and significant negative correlations emerged between SRL and the other three processes. Further multiple linear regression analysis revealed reappraisal, practice hours, and expertise accounted for 26% of the variance in SRL. Finally, a factorial (2x2x2) ANOVA yielded significant group differences on ER as a function of gender, expertise, and occupation. Results suggest that reappraisal can enhance the use of SRL in musicians, thus highlighting the potential utility in considering ER as part of SRL. These results suggest that by including training on emotion regulation strategies within musicians’ educational institutions and workplaces, efficiency and engagement in SRL can be enhanced. This could produce more effective learning strategies and outcomes, together with higher musical achievements.